PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI DIAGRAM BATANG SISWA KELAS IV MELALUI MEDIA PAPAN DIAGRAM (PADI) DI SDN KEBONSARI I SURABAYA - Vivi Nur Rofi’ah; Delia Indrawati; Ganda Riswanto; Sri Yuniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve the mathematics learning outcomes of fourth grade students at SDN Kebonsari I Surabaya which are still low, especially in bar diagram material using the Diagram Board (PADI) teaching aid media. This media is designed to make learning more interactive and concrete. in line with constructivist learning theory and Bruner's theory which emphasizes the importance of concrete experience in understanding abstract concepts. The research method applied is Collaborative Classroom Action Research (PTK.K) using the Kemmis and McTaggart model, which includes two cycles consisting of planning, implementation, observation and reflection. This research involved 26 class IV A SDN Kebonsari I Surabaya students as the main participants. The instruments used include observation sheets and essay tests to measure student learning outcomes. The results show a significant increase in student learning outcomes after using the Diagram Board (PADI) teaching aid media. In Cycle I, only 43% of students obtained a score above the KKM with a class average of 62.70. In Cycle II, all students (100%) succeeded in achieving a score above the KKM with a class average of 91.15. This increase shows the effectiveness of the Diagram Board (PAD) I teaching aid in increasing students' understanding of the concept of bar graphs. The use of the Diagram Board (PADI) teaching aid not only improves student learning outcomes but also encourages active participation and collaboration between students in study groups. This research suggests that teachers use interactive learning media more often to improve the quality of teaching and support the use of innovative media by schools to improve student learning outcomes. Further research is recommended to evaluate the effectiveness of this medium on various topics and grade levels.